Indexaçao de obras de ficçao em bibliotecas: avaliaçao e adequaçao do Modelo para Indexaçao de Ficçao (MENTIF) - Fujita, Mariângela Spotti Lopes (2017)
The Indexing of works of fiction to libraries catalogs requires an appropriate methodology linked to the textual structure of fiction narratives. The lack of an indexing methodology limits the representation and retrieval of subjects in the catalog. The methodological proposal of the Fiction Indexing Model (MENTIF) increases subject access points to the bibliographic records in the retrieval of these contents by other terms other than "fiction literature" representation. The research on indexing of works of fiction has as its objective to adjust the Model for Fiction Indexing (MENTIF) performed by researchers and catalogers. For this purpose, four evaluation stages were carried out, which included analysis of bibliographic records and the application of questionnaires to collect data regarding satisfaction and dissatisfaction. The results obtained allowed an adjustment of the MENTIF in accordance with the time restriction for the task as well as considering the catalogers cognitive and socio-cognitive strategies